2020
DOI: 10.1002/tpg2.20056
|View full text |Cite
|
Sign up to set email alerts
|

Making the most of all data: Combining non‐genotyped and genotyped potato individuals with HBLUP

Abstract: Using genomic information to predict phenotypes can improve the accuracy of estimated breeding values and can potentially increase genetic gain over conventional breeding. In this study, we investigated the prediction accuracies achieved by best linear unbiased prediction (BLUP) for nine potato phenotypic traits using three types of relationship matrices pedigree ABLUP, genomic GBLUP, and a hybrid matrix (H) combining pedigree and genomic information (HBLUP). Deep pedigree information was available for >3000 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The lower heritability estimates can be due to the underrepresentation of significant causal loci by markers (Speed et al, 2012) or dominance. Sood et al (2020) showed that narrow-sense heritability was moderate for eye depth, average tuber weight, and average tubers per plant. In our study, we obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The lower heritability estimates can be due to the underrepresentation of significant causal loci by markers (Speed et al, 2012) or dominance. Sood et al (2020) showed that narrow-sense heritability was moderate for eye depth, average tuber weight, and average tubers per plant. In our study, we obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies have explored the potential of implementing GS in potato breeding for different traits by determining the prediction accuracy (Slater et al, 2016; Sverrisdóttir et al, 2017; Enciso-Rodriguez et al, 2018; Endelman et al, 2018; Stich and Van Inghelandt, 2018; Sverrisdóttir et al, 2018; Caruana et al, 2019; Byrne et al, 2020; Gemenet et al, 2020; Sood et al, 2020; Wilson et al, 2021). Different degrees of prediction accuracies from low to high depending on the studied traits have been reported, which could be caused by the different genetic architectures, prediction models, but also the considered genetic material.…”
Section: Introductionmentioning
confidence: 99%
“…The more accurate the information used in breeder decisions, the more effective selection can be. This is particularly important as potato breeders begin implementing genomic selection cycles, where inaccurate predictions can drive populations in the wrong direction (Caruana et al 2019;Enciso-Rodriguez et al 2018;Endelman et al 2018;Gemenet et al 2020;Habyarimana et al 2017;Selga et al 2021;Sood et al 2020;Stich and Van Inghelandt 2018;Sverrisdóttir et al 2017;Sverrisdóttir et al 2018).…”
Section: Discussionmentioning
confidence: 99%